Reading the Bible ethically : recovering the voice in the text - Douglass, Eric J., M. Div. (Biblical Interpretation Series, 2014)
All interpretive systems deal with the author. Modern systems consider the text to be autonomous, so that it is disconnected from the author's interests. In Reading the Bible Ethically , Eric Douglass reconsiders this connection. His central argument is that the author is a subject who reproduces her culture and her subjectivity in the text. As the author reproduces her subjectivity, the text functions as the author's voice. This allows Douglass to apply ethical principles to interpretation, where that voice is treated as a subject for conversation, and not an object for manipulation. He uses this to texture the reading process, so that an initial reading takes account of the author's communication, while a second reading critiques that communication.